UPAYA GURU AKIDAH AKHLAK DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL (EQ) PESERTA DIDIK KELAS VIII B (Studi Kasus Di Mts Hidayatul Mubtadiin Kabupaten Lampung Selatan) - Suci Hartati (Journal of Islamic Education and Learning, 2022)
This research is entitled "The Efforts of Akhlak Teachers in Developing the Emotional Intelligence of Students at MTs Hidayatul Mubtadiin". , (2) What are the results of the Akidah Akhlak teacher in developing the emotional intelligence of students at MTs Hidayatul Mubtadiin Jatiagung. The objectives of this study are: (1) to determine and analyze teacher understanding in developing the emotional intelligence of students at MTs Hidayatul Mubtadiin Jatiagung, (2) to identify and analyze the efforts of teachers of aqidah akahlak in developing emotional intelligence of students at MTs Hidayatul Mubtadiin Jatiagung. The methodological approach taken in this investigation is a descriptive qualitative one. This study uses observation, interviews, and documentation to learn more about an individual who teaches moral aqidah. Both primary and secondary sources were used to collect information for this study. Pedagogical, psychological, and social research methods were employed in this study. Data processing and analysis are two of the most common methods of handling large amounts of data. This research confirmed the importance of the moral aqidah teacher's work in fostering the students' emotional intelligence at MTs Hidayatul Mubtadiin Jatiagung in South Lampung Regency. Some students at Mts Hidayatul Mubtadiin are less disciplined, fearful, anxious, worried, unmotivated, and overly angry, while others are more emotionally intelligent and can manage their emotions well, motivate themselves, and get along well with others. Teachers in Akidah Akhlak make an effort to cultivate their students' emotional intelligence in a number of ways, including: gaining insight into their students' personalities and emotions; guiding and motivating their charges; incorporating emotional intelligence-building activities into their Akidah Akhlak lessons; and punishing those who disobey the school's rules